Analysis of the variations of measured values in continuous long-term geodetic monitoring - Jan Vaněček (Geoinformatics FCE CTU, 2016)
A geodetic measurement of shifts and deformations by total station is a well-known and widely used method. There is presented the analysis of the variations over time of the measured values in continuous geodetic monitoring in this paper. There are used measured data from a specific monitoring system of a surface mine in the time period from January 2006 to July 2010 in the analysis. The aim of the analysis is to describe linear trend and periodic changes in measured data (horizontal direction, zenith angle and slope distance). The main method of the analysis is a linear-harmonic function approximation.